(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The term ‘anencephaly’ is commonly used for the serious developmental defect of the central nervous system, in which the brain and skull are completely or partially absent. The cases of anencephaly are not uncommon in the Department of Gynecology and Pediatrics but it is rarely noticed in practice of forensic medicine. One such rare case of anencephaly was brought to us in the Department of Forensic Medicine at Government Medical College, Vadodara (Gujarat), for autopsy examination in which the death was alleged due to malnutrition. After autopsy examination, we concluded that it was a case of anencephaly in which the brain was almost completely absent in the thick and malformed skull. The case is presented here with the aim to discuss its different medicolegal aspects as it is rare of its kind in our field.